Exploring pre-service teachersʼ and comprehensive school pupilsʼ understandings of literacies in digital environments - Hankala, Mari; Kankaanranta, Marja; Rousi, Rebekah; Mehtälä, Saana; Merjovaara, Olli (Universitetsforlaget, 2023)
This study focuses on Finnish pre-service teachersʼ and comprehensive school pupilsʼ understandings of literacies in digital environments. The study included 181 participants: 38 pre-service teachers, 79 primary school (PS) pupils and 64 lower secondary school (LS) pupils. The pre-service teachers created concept maps and written descriptions that portrayed their understanding of reading literacy, digital literacy and multiliteracy. The pupils were asked to write down what kinds of literacies they need in digital environments. The results indicate that the pre-service teachers mainly understood the many modalities of literacies. However, they emphasised reading literacy as the fundamental basis of other literacies. Similarly, the PS pupils perceived the many modalities of literacies, especially emphasising their visual elements. Instead of noticing the diversity of texts, LS pupils highlighted critical attitude and language skills.
Keywords: Pre-service teacher; comprehensive school pupil; digital environment; reading literacy; digital literacy; multiliteracy; fi=Viestintätieteet|en=Communication Studies|